(untitled) (Hungarian Journal of Industry and Chemistry, 2011)
The trace analysis of metal-complexes has long been an area of interest for analytical chemists and environmental researchers due to the biological and toxic properties of these compounds. The method for the simultaneous separation of the metal cations and organic and inorganic anions is based on the use of strong chelating anion with high charge. When basic solution contains an excess of strong complexing anion of high charge, such as ethylenediaminetetraacetate (EDTA) or trans-1,2-diamine-cyclohexane-tetraacetic acid (DCTA) ion, most heavy and transition metal ions will occur as anionic complexes. Hence this method provides simultaneous metal and anion separation. The EDTA and DCTA chelating agents exhibit strong complexing power. These aminopolycarboxylic acids can remobilize metals in nature. Because aminopolycarboxylic acids are a potential risk to the environment, it is important to develop an effective analytical technique for their determination. Several factors affect the retention in the separation of the complex anions: complex formation reactions, ion-exchange equilibria and protolysis depending on pH. The aim of this work is the optimization of a simultaneous chromatographic separation and identification of metal ions complexed by the ligand EDTA or DCTA. The method was utilized to separate CuEDTA2-, CuDCTA2-, ZnEDTA2-, ZnDCTA2-, AlEDTA-, AlDCTA-, Cl-, piruvate and maleate anions. An advantage of the developed method is that the same basic pH-range is favourable to the stability of the metal complexes and to the elution.